Lower urinary tract functions in a series of Charcot–Marie–Tooth neuropathy patients. (13th August 2013) - Krhut, J.; Mazanec, R.; Seeman, P.; Mann‐Gow, T.; Zvara, P.
<x xml:space="preserve">Abstract</x> Objectives To evaluate lower urinary tract (LUT), bowel, and sexual dysfunctions in a series of patients with Charcot–Marie–Tooth disease (CMT). Materials and Methods A cohort of 58 patients and 54 healthy controls filled out the International Prostate Symptoms Score (IPSS) and the International Consultation on Incontinence Modular (ICIQ) Questionnaires to assess their symptoms and their impact on the patient's quality of life. Results On the IPSS questionnaire, CMT patients reported a significantly higher score compared with the healthy controls in 7 of 8 questions. The ICIQ‐male LUT symptoms questionnaire revealed a significantly higher score in 7 of 26 questions. In the ICIQ‐female LUT questionnaire, a significantly higher score was observed in 13 of 24 questions. When assessing the bowel function in CMT patients using the ICIQ‐bowel questionnaire, a significantly higher score in 30 of 40 questions was noted. No differences in sexual function were found in either group. Conclusions The occurrence of the LUT symptoms and bowel dysfunctions in CMT patients was significantly higher when compared with an age‐matched control group. The symptoms were more frequent in female patients. The findings suggest that autonomic dysfunction should be evaluated and included in the diagnostic approach and care of CMT patients.